Horn antennas with enhanced functionalities through the use of frequency selective surfaces - Mahouti, Peyman; Gunes, Filiz; Belen, Mehmet Ali; Caliskan, Alper; Demirel, Salih; Sharipov, Zafar (WILEY, 2016)
In this work, realizations of a dual function integrated modules are simply built by fixing the identical frequency selective surface (FSS) s into the apertures of the available exponentially tapered transverse electromagnetic (TEM) and ridged horn antennas. Both modules are confirmed experimentally to have functions of prefiltering suppressing EMI and noise when the signal is received, alongside the enhanced directivity in the desired band, thus these modules can be called as Filtennas. A FSS is simply built by the properly designed periodic double anchor-shaped microstrip patches in CST microwave suit using low-cost FR4 with the relative permittivity 4.4, thickness 1.58 mm, loss tangent 0.0035. From the measured results, it can be found that the proposed modules keep mismatching characteristics of the horn antennas, meanwhile their gains and beamwidths are enhanced to amplify the signal in the desired band and simultaneously deteriorated to attenuate EMI and noise in the out-band. It is expected that this methodology can be implemented to effectively reduce volume and cost of communication systems. (c) 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:287-293, 2016.
Keywords: filtenna; frequency selective surface; horn antenna; performance enhancement; broad-band; Computer Science; Engineering